Fossil isotope evidence for trophic simplification on modern Caribbean reefs - Jessica A. Lueders-Dumont; Aaron O’Dea; Erin M. Dillon; Brigida de Gracia; Chien-Hsiang Lin; Sergey Oleynik; Seth Finnegan; Daniel M. Sigman; Xingchen Tony Wang (Nature, 2026)
Abstract Caribbean reefs have experienced major human-driven changes to their coral and fish communities 1–4 , yet how these changes have affected trophic dynamics remains poorly understood owing to challenges in reconstructing the trophic structure of pre-human-impact reefs. Advances in fossil-bound protein nitrogen isotope ( 15 N/ 14 N) analysis now enable the reconstruction of ancient trophic dynamics 5,6 , as the 15 N to 14 N ratio reflects an animal’s trophic position 7 . Here we apply this method to modern and prehistoric (7,000-year-old) fish otoliths (ear stones) and corals from Caribbean Panama and the Dominican Republic, focusing on fishes occupying low to middle trophic levels. We find that although the trophic level typically declined in high-trophic-level fishes over time, it increased or remained unchanged in low-trophic-level fishes, indicating that modern food chains are 60–70% shorter than on the prehistoric reefs in both Panama and the Dominican Republic. Furthermore, across all trophic groups, we observed a marked reduction in dietary variation, with a 20–70% lower trophic range on the modern reefs compared to the prehistoric reefs. This pattern is best explained by less dietary specialization in modern reefs, consistent with less ecological complexity than in prehistoric reefs. These differences document and quantify the trophic simplification that has occurred on modern Caribbean reefs, a change that may increase their vulnerability to ecosystem collapse.